Intervenciones de enfermería en adultos mayores con neumonía: revisión sistemática - Guacho Janeta, Sonia Vanessa (2025)
Introduction: Respiratory infections, including pneumonia, are a high risk for elderly people due to physical vulnerability. The effectiveness of nursing interventions largely depends on adherence to protocols, which are crucial for preventing complications and improving quality of life. Objective: To describe and evaluate nursing interventions in improving clinical outcomes and quality of life for elderly people with pneumonia through a systematic review of existing scientific literature. Methodology: A qualitative study was conducted using the PRISMA methodology to systematically review 26 selected scientific articles and theses. The databases consulted included Scielo, PubMed, ScienceDirect, among others. Results: The systematic review revealed that nursing interventions, especially those related to aseptic practices and personalized care, are essential for reducing the incidence of respiratory infections in elderly people. However, the effectiveness of these interventions varies according to adherence to protocols and staff training. The data indicate that better training and clear protocols significantly improve clinical outcomes and reduce mortality in patients with pneumonia. Conclusion: It is essential to strengthen training in pneumonia prevention for staff, patients, and caregivers to ensure adherence to protocols, optimize clinical outcomes, and improve the quality of life for these patients. The systematic review provides a solid foundation for future research and improvements in clinical practices in this field.